Original paperHigh resolution (3 Tesla) MRI-guided conformal brachytherapy for cervical cancer: consequences of different high-risk CTV sizes - Anderson, James W.; Xia, Junyi; Flynn, Ryan T.; Modrick, Joseph M.; Bhatia, Sudershan K.; Jacobson, Geraldine M.; Kim, Yusung (Journal of Contemporary Brachytherapy, 2013)
Purpose : To evaluate conventional brachytherapy (BT) plans using dose-volume parameters and high resolution (3 Tesla) MRI datasets, and to quantify dosimetric benefits and limitations when MRI-guided, conformal BT (MRIG-CBT) plans are generated. Material and methods : Fifty-five clinical high-dose-rate BT plans from 14 cervical cancer patients were retrospectively studied. All conventional plans were created using MRI with titanium tandem-and-ovoid applicator (T&O) for delivery. For each conventional plan, a MRIG-CBT plan was retrospectively generated using hybrid inverse optimization. Three categories of high risk (HR)-CTV were considered based on volume: non-bulky ( 20 cc and < 40 cc) and bulky (≥ 40 cc). Dose-volume metrics of D 90 of HR-CTV and D 2cc and D 0.1cc of rectum, bladder, and sigmoid colon were analyzed. Results: Tumor coverage (HR-CTV D 90 ) of the conventional plans was considerably affected by the HR-CTV size. Sixteen percent of the plans covered HR-CTV D 90 with the prescription dose within 5%. At least one OAR had D 2cc values over the GEC-ESTRO recommended limits in 52.7% of the conventional plans. MRIG-CBT plans showed improved target coverage for HR-CTV D 90 of 98 and 97% of the prescribed dose for non-bulky and low-bulky tumors, respectively. No MRIG-CBT plans surpassed the D 2cc limits of any OAR. Only small improvements (D 90 of 80%) were found for large targets (> 40 cc) when using T&O applicator approach. Conclusions : MRIG-CBT plans displayed considerable improvement for tumor coverage and OAR sparing over conventional treatment. When the HR-CTV volume exceeded 40 cc, its improvements were diminished when using a conventional intracavitary applicator.